The Matilda Effect: Underrecognition of Women in Hematology and Oncology Awards. (9th July 2021) - Patel, Shruti R.; St. Pierre, Frederique; Velazquez, Ana I.; Ananth, Snegha; Durani, Urshila; Anampa-Guzmán, Andrea; Castillo, Katerina; Dhawan, Natasha; Oxentenko, Amy S.; Duma, Narjust
Abstract : Background: The proportion of women in the field of hematology and oncology (H&O) has increased over recent decades, but the representation of women in leadership positions remains poor. In an effort to close the gender gap in academia, it is important to report on such inequities in hopes to close these gaps and improve career development. Materials and Methods : We conducted a retrospective, observational study of published award recipients from 1994 to 2019 from the seven major H&O societies in the world. Gender was determined based on publicly available data. The χ 2 and Cochran-Armitage tests were used for data analysis. Results: Of the 1, 642 awardees over the past 26 years, 915 met inclusion criteria. Award recipients were overwhelmingly men (77.9%) and non-Hispanic White (84.7%). Women awardees received 30.3% of the humanistic and education-related awards, whereas only receiving 16.0% of basic science awards ( p < .01). Women represent 35.6% of all hematologists and oncologists but only received 24.0% of awards given to these physicians ( p = .004). Black, Hispanic, and Asian awardees represented 3.7%, 3.3%, and 6.8% of the total awardees, respectively. Conclusion: From 1994 to 2019, women were less likely to receive recognition awards from the seven major H&O societies studied compared with men. We also observed a considerably low proportion of minority awardees across all oncology subspecialties. Further studies examining how selection criteria favor either gender would be warranted in order to achieve equal representation in academic awards. Implications for Practice: In this study, women and minority groups were found to be underrepresented amongst award recipients. Significant disparities were seen in disciplines that have been historically male predominant, such as basic sciences. As awards on an international level enhance academic resumes and assist with career advancement, it is important that awards are being given in an equitable manner. First steps to promote diversity and inclusion in academic medicine is reporting of gender and racial disparities in various areas of academia. Abstract : This article examines gender and race representation of award recipients from the seven major international hematology and oncology societies.